2018
DOI: 10.1186/s40537-018-0156-1
|View full text |Cite
|
Sign up to set email alerts
|

Automatic schema suggestion model for NoSQL document-stores databases

Abstract: New generation databases also called NoSQL (Not only SQL) databases are highly scalable, flexible, and low-latent. These types of databases emerge as a result of the rigidity shown by traditional databases to handle today's data which is voluminous, highly diversified and generated at a very high rate. With NoSQL, problems such as database expansion difficulties, low query performance and low storage capacity are addressed. However, the inherent complexity of contemporary datasets coupled with programmers' low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 17 publications
0
9
0
2
Order By: Relevance
“…A small scale of DSP was originally introduced in an earlier article [24,25] as SPM. In this extended presentation, we focus on one impotent parameter (i.e., performance) and also describe how DSP supports a broader class of query complexities, like single-selectivity, drill-down, and rollup.…”
mentioning
confidence: 99%
“…A small scale of DSP was originally introduced in an earlier article [24,25] as SPM. In this extended presentation, we focus on one impotent parameter (i.e., performance) and also describe how DSP supports a broader class of query complexities, like single-selectivity, drill-down, and rollup.…”
mentioning
confidence: 99%
“…In [55] A schema was suggested for the document-based database in three areas of NoSQL, namely architecture, algorithm, and association rules. The purpose of this model was to maintain a balance of compatibility, availability, and scalability features in the data model.…”
Section: Review Of the Selected Articlesmentioning
confidence: 99%
“…• Scalability: The data model efficient performance on multiplied size or scale • Performance: The data model efficiency in terms of data production volume and velocity and big data processing The determining factors in data model design are considered consistency, availability, and scalability [55]. Having reviewed various articles, we observed that scalability, performance, and schema-less with frequencies of 10% or more are important features in designing the data model (Figure 9).…”
Section: B Data Model Featuresmentioning
confidence: 99%
“…In a different study, Imam et al 16 presented a schema suggestion model for NoSQL document‐model databases. The proposed model suggests a schema based on system requirements and parameters such as list of entities and CRUD (Create, Read, Update and Delete) statements which are used in the production of NoSQL database schemas.…”
Section: Related Workmentioning
confidence: 99%
“…There has been little research done on automatic database schema design for NoSQL non‐relational databases 12‐20 . All of the studies take an offline approach to the schema design problem and are not able to monitor the managed database system in order to detect changes and adapt the schema design accordingly.…”
Section: Introductionmentioning
confidence: 99%